Monetary Policy Challenges and Central Bank Independence in Uzbekistan’s Inflation Targeting Transition: Tantangan Kebijakan Moneter dan Independensi Bank Sentral dalam Transisi Penargetan Inflasi di Uzbekistan - Ganieva, Umida Abdugaffarovna (Academia Open, 2024)
This article examines second language learning ability by analyzing second language development. It also examines the age factor in learning a language other than the mother tongue and attempts to clarify whether there is currently sufficient evidence to show that young people undergo real changes in their language skills.. Research such as inspiration for the learning climate, as well as exposure and behavior in the language will also be addressed and data analyzed to assess if they play an essential role in encouraging students to achieve effective second language skills. It was widely known to create a big improvement in language learning when you are young to study a second language. However, the findings show that this is not completely applicable in all situations, provided that other considerations such as language sensitivity and enthusiasm influence the effective accomplishment of second-language learning. If vocabulary is lacking, therefore this could discourage students from studying the language effectively. However, it is worth noting that factors such as motivation and exposure play a more important role in the learning stage than the aging factor. This empowers the learner because, regardless of his age, it is extremely important for him to be motivated enough and have enough language exposure from the beginning. Highlights: Analyzes second language development and age factor in language learning. Highlights motivation, exposure, and behavior's impact on effective language skills. Motivation and exposure outweigh age in successful second-language acquisition. Keywords: Uzbekistan, Inflation Targeting, Monetary Policy, Central Bank Independence, Monetary Policy Transmission, Financial System Health